Effects of two different knee tape procedures on lower‐limb kinematics and kinetics in recreational runners. Issue 4 (2nd July 2014) - Howe, A.; Campbell, A.; Ng, L.; Hall, T.; Hopper, D.
<x xml:space="preserve">Abstract</x> The purpose of this study was to compare the effects of Mulligan's tape (MT) and kinesio tape (KT) with no tape (NT) on hip and knee kinematics and kinetics during running. Twenty‐nine female recreational runners performed a series of 'run‐throughs' along a 10‐m runway under the three taping conditions. Two force plates and a 14‐camera Vicon motion analysis system (Oxford Metrics, Inc., Oxford, UK) captured kinematic and kinetic data for each dependent variable from ground contact to toe off. Comparisons of each dependent variable under three taping conditions were assessed through Statistical Package for the Social Sciences (SPSS; SPSS, Inc., Chicago, Illinois, USA; P‐value < 0.01) using repeated measure analyses of variance. For each dependent variable with a P‐value < 0.01, repeated measures with pairwise comparisons and Bonferroni adjustment were conducted to compare the three taping conditions. MT induced a significant reduction in anterior and posterior hip forces, knee flexion angular velocity, knee extensor moments, and hip flexion and extension moments compared with NT and KT (P = 0.001). There was no difference in hip or knee, kinematics or kinetics, between KT and NT (P = 1.000). MT appears to influence hip and knee biomechanics during running in an asymptomatic sample, whereas KT appeared to be biomechanically not different from NT.